Pengembangan Media Perangkat LKPD (Lembar Kerja Peserta Didik) Berbasis Multiple Intellegence Pada Materi Laju Reaksi Di SMA Dian Harapan Holland Village - Dachi, Asna Tri Putry; Karundeng, Marlina; Lombok, Johny Z. (General Chemistry Journal, 2024)
The learning process is an interaction between educators and students in order to achieve learning objectives. As educators, of course, they must understand the needs of students in the learning process, if the methods taught are appropriate and effective, it will have a good impact on student learning outcomes. The purpose of this study is to develop a learning media and find out the feasibility of the media. This research method is Research and Development with the aim of developing and producing a device media product. The results of media expert validation research, material and media trials on students show that LKPD based on multiple intelligence on reaction rate material has met the criteria or indicators. The conclusion in this study is that the media expert feasibility test score of 84% of the feasible category, the material expert test score of 96% of the very feasible category, and the response of students with an average of 90% of the attractive category